Kepemimpinan politik kepala desa - Dwinugraha, Akbar Pandu (Universitas Merdeka Malang, 2020)
This study looks at the leadership of the village head in building communication, direct relationships and the formulation of authority and responsibility in the administration of village governance. This type of combination research was used in this study which resulted in the conclusion that most of the leadership of the village head with stakeholders including traditional leaders, religious leaders, community leaders, women's groups, BPD and LPMD had been going well. Although the process of building good relations with former political opponents was still an obstacle, especially in the original village cluster. Second, the leadership of the village heads in the three village clusters was of various types where the first cluster seemed liberal, middle democratic and continued democratic-autocratic. Third, the direct relationship between the village head and subordinates as well as the community in the three village clusters has been well established in terms of providing information, coordination, openness and transparency, although community trust in openness and transparency is seen as good only in villages with advanced clusters. Fourth, the formulation of powers and responsibilities of village heads in the three village clusters shows that the higher the village cluster the formulation of authority is more focused on the figure of the village head.